2019
DOI: 10.1016/j.fsigen.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of DNA mixture to mixture matching

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  We investigate a method to identify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This was later extended to include forward stutter (with modelling of forward stutter described in [157,158]), and then generalised so that any number of stutters (and with any size-based relationship to the parent peak), applied to any combination of specific loci, could be added by users with the mathematical framework automatically extending to incorporate them (generalised stutter modelling is described in [155]). The height of coincident peaks (either from multiple allele donations, or allele and stutter) are added [159,160] to produce the final expected peak heights.…”
Section: Deconvolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was later extended to include forward stutter (with modelling of forward stutter described in [157,158]), and then generalised so that any number of stutters (and with any size-based relationship to the parent peak), applied to any combination of specific loci, could be added by users with the mathematical framework automatically extending to incorporate them (generalised stutter modelling is described in [155]). The height of coincident peaks (either from multiple allele donations, or allele and stutter) are added [159,160] to produce the final expected peak heights.…”
Section: Deconvolutionmentioning
confidence: 99%
“…Two mixtures can be compared using DBLR in order to determine whether there is support for a common DNA donor, using the method described by Slooten [20]. Studies into this feature have found a high efficacy for identifying common donors [159]. The process has been shown to have use as a Quality Assurance tool to identify potential sample to sample contamination events [25].…”
Section: Dblr-a Companion Product To Strmix™mentioning
confidence: 99%
See 1 more Smart Citation
“…A mixture-to-mixture comparison was carried out (as per the method in [12,13]) and an LR calculated considering the propositions:…”
Section: -Dna Resultsmentioning
confidence: 99%
“…The probability associated with matching background DNA profile is typically set quite low, due to the discrimination power of DNA profiling systems. The value can be assigned based on a match probability if the unknowns are able to be interpreted, or could be based on mixture to mixture comparisons [12,13] if the unknowns are not resolvable. When common unknown donors are found to be present, the evaluation will show that the findings provide strong support for the presence of the alternate offender, as the probability of transfer, persistence and recovery of the DNA of that donor is much higher than matching profiles from different sources present as background.…”
Section: Introductionmentioning
confidence: 99%